English grammar for ESL learners - Swick, Ed Edward (New York McGraw Hill, 2022)
"For clear, precise explanations of all aspects of English grammar, look no further than [this book]! As a beginning learner of English, you might find that grammar concepts can be confusing. To make progress with your English skills, you need guidance through tricky grammar areas. This book will help develop mastery. The more you practice, the more you become proficient in how you use English. [This book] will help increase your confidence in writing and communicating in English by helping you understand the different rules and elements of grammar, broaden your knowledge with sentence rewrites and creative writing prompts, build your grammar skills with more than 120 engaging exercises, [and] test your overall comprehension with a comprehensive review section"--Back cover.
Nouns -- Definite and indefinite articles -- Adjectives -- Personal pronouns -- Verbs -- Auxiliary verbs -- Passive voice -- Subjunctive mood -- Adverbs -- Review Exercises 1 -- Contractions -- Plurals -- Punctuation -- Infinitives and gerunds -- Relative pronouns -- Reflexive pronouns -- Possession -- Possessive pronouns -- Prepositions -- Capitalization -- Review exercises 2 -- Comparative and superlative forms -- Conjunctions -- Interrogatives -- Negation -- Numbers -- Some important contrasts -- Review exercises 3 -- Appendix: Common irregular verbs -- Answer key.
"The bonus app that accompanies this book provides: streaming audio recordings of answers to 100 exercises from the book, record yourself to model your pronunciation after native speakers, 40 review quizzes to test your mastery of all key concepts"--Back cover.
Keywords: English language -- Textbooks for foreign speakers; English language -- Grammar -- Problems, exercises, etc